The Effect of Recognition of Revenue, Contract Liabilities and Contract Assets Under Psak 72 on Financial Performance of Telecommunication Companies Listed on The Idx for The 2015-2020 Period - Masril, Masril; yusuf, muhammad; Novianti, Dian (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
PSAK 72 has been established as the single accounting standard for revenue recognition from contracts with customers which officially replaces all standards related to revenue recognition. Recognition of revenue under PSAK 72 will also result in the recognition of contract liabilities and contract assets. PSAK 72 can now be applied early with the active year January 1, 2020. The financial performance of telecommunications companies is calculated using financial ratios, namely the activity ratio (total asset turnover). Researchers used secondary data sources in the form of financial reports with data collection techniques, namely documentation. The population of this research is 11 companies using purposive sampling technique so that the research sample becomes 7 telecommunications companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The analytical technique used is descriptive statistical analysis and analyzed through multiple linear regression to test the effect of the independent variable on the dependent variable. The results of the study partially recognize contract liabilities have no effect on the financial performance total asset turn over, while the income variable has a partial and significant effect on the financial performance of total asset turnover and contract asset variable has a partial but no significant effect on the total asset turn over. The results of the study show that simultaneous revenue recognition, contract liabilities and contract assets simultaneously and significantly affect the financial performance of total asset turnover.